2011
DOI: 10.1007/s10508-011-9846-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Alcohol and Sexual Arousal on Determinants of Sexual Risk in Men Who Have Sex with Men

Abstract: Primary prevention efforts aimed at sexual risk behaviors are critical. This experiment was designed to investigate the effects of alcohol intoxication and sexual arousal, as well as person variables of alcohol sex expectancies and attitudes toward condom use, on hypothesized determinants of sexual risk behaviors among men who have sex with men (MSM). The participants were 117 MSM aged 21–50 years who were randomly assigned to one of six separate experimental conditions created by the combination of beverage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
74
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 50 publications
8
74
2
Order By: Relevance
“…2,3 The acute effects of alcohol consumption (e.g., altered cognition, impaired judgment, and increased sexual desire and confidence) may contribute to risk-taking behaviors. [4][5][6][7] A myriad of psychosocial factors (e.g., cognitive escape, impulsivity, expectancies) are believed to mediate the association between alcohol and sexual risk behaviors. 5,[8][9][10][11][12][13] Furthermore, bar and club venues frequented by MSM provide conducive environments for both meeting sexual partners and binge drinking.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The acute effects of alcohol consumption (e.g., altered cognition, impaired judgment, and increased sexual desire and confidence) may contribute to risk-taking behaviors. [4][5][6][7] A myriad of psychosocial factors (e.g., cognitive escape, impulsivity, expectancies) are believed to mediate the association between alcohol and sexual risk behaviors. 5,[8][9][10][11][12][13] Furthermore, bar and club venues frequented by MSM provide conducive environments for both meeting sexual partners and binge drinking.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies using global measures have generally linked various alcohol-related variables to risky sexual outcomes in MSM (2022), with some exceptions (2326). Although preliminary, one published experimental study examining the alcohol-risky sex link among MSM supported an association between alcohol intoxication and intentions to engage in unprotected anal intercourse (UAI) (27). Finally, in contrast to research in heterosexual populations, a recent review of event-level studies concluded that, across several studies of MSM specifically, binge alcohol use was consistently related to sexual risk outcomes such as UAI (28).…”
Section: Introductionmentioning
confidence: 99%
“…Participants who were older were less likely to report substance abuse in the past three months (AOR = 0.93, 95% CI = 0.89, 0.97) and participants reporting increased depressive symptoms were more likely to report substance abuse (AOR = 1.05, 95% CI = 1.01, 1.09). The findings from this study supports previous research findings linking depressive symptoms with substance use/abuse in Hispanic men (Gonzalez-Guarda, Florom-Smith, & Thomas, 2011;Gonzalez-Guarda et al, 2010;Maisto, Palfai, Vanable, Heath, & Woolf-King, 2012). Additionally, this contradicts this study's proposed hypothesis that increased age in middle age HMSM may increase risk for depression; however, this study was not exclusively middle age HMSM.…”
Section: Depressive Symptoms In Hispanic Men Who Have Sex With Men (Hsupporting
confidence: 90%
“…In a study by Maisto et al (2012) Post-hoc analyses reported that the high conflict/high expectancy participant group engaged in a significantly higher percentage of their sexual acts under the influence than the high conflict/low expectancy group (P < 0.01), and the low conflict/low expectancy group (P = 0.048), signifying participants high in conflict appear more sensitive to the effect of expectancies, compared to their low conflict counterparts (Well et al, 2011).…”
Section: Substance Use/abuse In Men Who Have Sex With Men (Msm)mentioning
confidence: 94%
See 1 more Smart Citation